Cohort Profile: Effective Perinatal Intensive Care in Europe (EPICE) very preterm birth cohort - Zeitlin, J (2020)
The EPICE cohort is a geographically defined study of still-births and live births from 22 þ 0 to 31 þ 6 weeks of gestation in 19 European regions (Fig. 1). Regions were selected with respect to geographic and organizational diversity and feasibility, meaning they had systems for collecting population data on VPT babies that could be modified to integrate the study protocol. In France, the EPICE study includes three regions of the national EPIPAGE 2 cohort study. Participating regions started data collection between March and July 2011 and the inclusion period lasted 12 months, except in France where it was 6 months. The study also collected information from the hospitals where these children were born and hospitalized. Questionnaires were sent to neonatal units with at least 10 VPT admissions and their associated maternity units in the spring of 2012. Investigators abstracted data from medical records in obstetric and neonatal units for all births with a gestational age between 22 þ 0 and 31 þ 6 weeks. Gestational age was defined as the best obstetric assessment based on information on last menstrual period and antenatal ultrasounds, which are part of routine obstetric care in all regions. Inclusions were cross-checked against delivery ward regis- ters or another external data source.